Exploring Critical Factors of Crowd-Based Requirement Engineering Using Fuzzy DEMATEL-ANP Method - Rida Fatima; Khubaib Amjad Alam; Ansar Siddique; Talha Mahboob Alam; Kamran Shaukat (IEEE Access)
The elicitation of software requirements through the crowd has become an effective approach for requirements development. This approach could improve the quality of the requirement elicitation process, which is a daunting requirement engineering activity. Crowd-based requirement engineering (CrowdRE) has proven beneficial for several systems, specifically those involving diverse stakeholders. This study intends to identify and prioritise the critical factors related to the CrowdRE process through a hybrid Multi-Criteria Decision Making (MCDM) method called DEMATEL-ANP. Hence, in the first place, an extensive literature review was carried out to determine important factors that greatly affect the CrowdRE approach. Secondly, amid the recognised factors, only those with high frequency in the literature were considered for further analysis. The study employs MCDM methods due to their ability to rank and evaluate conflicting alternatives based on expert opinion. Among MCDM techniques, Fuzzy DEMATEL-ANP was chosen, where DEMATEL finds the importance, interrelations, and cause & effect of factors, and ANP assesses relative weights. The fuzzy approach was applied to handle the vagueness and uncertainty among expert opinions. The research results are processed with the help of a custom-developed tool that automates the methods and operations. A comparative analysis was performed to evaluate the performance of Fuzzy and conventional DEMATEL-ANP. The results revealed that Competence is the most important factor, followed by feedback, whereas Anonymity is the least significant factor; thus, it can be excluded from the final list of factors. Among the interrelated factors, competence and feedback were correlated factors of CrowdRE. Moreover, the factors are categorised into cause-and-effect groups. The cause group contains largeness, anonymity, and diversity factors and is termed an influencing factor. The effect group consists of feedback, motivation, competence, and collaboration, known as influencing factors.